PENGARUH BOARD DIVERSITY TERHADAP NILAI PERUSAHAAN : STUDI KASUS PADA PERUSAHAAN SEKTOR PROPERTY & REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Novrianti, Mesy; Isynuwardhana, Deannes (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
The research aims to determine the effect of gender diversity, nationality of commissioners, education of commissioners, age of commissioners, and independent commissioners on firm value. This research uses a quantitative method with secondary data using E-views 12 software to conduct the research hypothesis testing. The population in this study are Property & Real Estate sector companies listed on the Indonesia Stock Exchange for the period 2018-2022. The sampling technique used is purposive sampling, and the selected sample size is 46 companies, with a total of 230 observation data. This research is analyzed using descriptive statistics and panel data regression. The results of this study indicate that partially, the gender diversity variable has a positive effect on firm value, while the variables of commissioner nationality, commissioner education, commissioner age, and independent commissioners do not affect firm value.